APPLICATION OF THE STUDENT FACILITATOR AND EXPLAINING (SFE) MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN INTERNET ACCESS MATERIALS IN CLASS XI IPS 1 SMA NEGERI 1 PURI - Purwoko Hadiwasito (Jurnal Scientia, 2022)
The results of the initial observations showed that the learning outcomes of students' internet access materials in class XI IPS 1 of SMA Negeri 1 Puri with completeness were only 62.1%. The low learning outcomes are due to the application of learning models that are not suitable, students are passive in learning. The purpose of this study was to analyze the improvement of learning outcomes for class XI IPS 1 SMA Negeri 1 Puri through the application of the Student facilitator and explaining (SFE) learning model. This classroom action research consists of two cycles consisting of planning, implementation, observation and reflection stages. The subjects of this study were students of SMA Negeri 1 Puri class XI IPS 1 for the 2018/2019 academic year which consisted of 32 students. Based on the results and discussion, it can be concluded that learning using the Student Facilitator and explaining (SFE) learning model provides convenience for teachers in learning, makes learning student-centered, completes learning outcomes, and can teach and practice student character behavior.